2019
DOI: 10.1111/1460-6984.12493
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and stability of the metrical stress effect on segmental production accuracy in persons with apraxia of speech

Abstract: Background: Acquired apraxia of speech (AOS) involves speech-production deficits on both the segmental and suprasegmental levels. Recent research has identified a non-linear interaction between the metrical structure of bisyllabic words and word-production accuracy in German speakers with AOS, with trochaic words (strong-weak stress) being resistant to errors compared with iambic words (weak-strong). Aims: To replicate previous findings in English speakers with AOS, to measure the test-retest reliability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
(47 reference statements)
2
2
0
Order By: Relevance
“…The effect was small in the healthy participants and the Parkinson’s patients and much larger in the two patient groups with AOS or phonological impairment after left hemisphere lesions, and it was independent of the regularity of the prime sentences. For patients with AOS, this result confirms earlier investigations based on repetition tasks, which revealed an advantage of trochaic over iambic patterns [ 35 , 36 , 37 ]. Furthermore, the results are in agreement with the error data reported from the same experiment for patients with AOS and PI [ 76 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The effect was small in the healthy participants and the Parkinson’s patients and much larger in the two patient groups with AOS or phonological impairment after left hemisphere lesions, and it was independent of the regularity of the prime sentences. For patients with AOS, this result confirms earlier investigations based on repetition tasks, which revealed an advantage of trochaic over iambic patterns [ 35 , 36 , 37 ]. Furthermore, the results are in agreement with the error data reported from the same experiment for patients with AOS and PI [ 76 ].…”
Section: Discussionsupporting
confidence: 90%
“…They therefore seemed to exploit natural rhythmic cues in heard speech for the segmental realization of the target words. Furthermore, our study confirmed earlier results showing that the symptoms of AOS can be modulated positively by a regular (trochaic) stress of words to be produced [ 35 , 36 ]. The benefit from the regularity of target words could, for the first time, also be demonstrated in individuals with PI.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most notably, the iambic patterns led to greater numbers of segmental errors, which pointed at an interlacing of segmental with supra-segmental levels of speech motor planning. This effect has meanwhile been replicated for American English (Bailey, Bunker, Mauszycki, & Wambaugh, 2019). By inference, although most apraxic speech errors surface as segment-bound symptoms, as in the examples (1) above, the source of these errors does not necessarily have to be assigned to the affected phonemes themselves, but can also lie at some higher, e.g., syllabic or metrical level of articulation planning.…”
Section: Factors That Influence Apraxic Speech Errorsmentioning
confidence: 82%